The making of an economic superpower unlocking China's secret of rapid industrialization - Wen, Yi (World Scientific Pub., 2016)
The rise of China is no doubt one of the most important events in world economic history since the Industrial Revolution. This book argues that only a radical reinterpretation of the history of the Industrial Revolution and the rise of the West (as incorrectly portrayed by the institutional theory) can fully explain China's growth miracle and why the determined rise of China is unstoppable despite its current "backward" financial system and political institutions.